2014
DOI: 10.1111/jac.12090
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Rht‐B1 Dwarfs Exhibit Better Photosynthetic Response to Water Deficit at Seedling Stage Compared to the Wild Type

Abstract: Wheat reduced height (Rht) genes encode modified DELLA proteins, which are gibberellin insensitive, accumulate under stress, restrain growth and affect plant stress response. The seedling reaction to soil water deficit regarding leaf gas exchange and chlorophyll fluorescence was compared in near-isogenic lines carrying the alleles Rht-B1a (tall), Rht-B1b (semi-dwarfing) and Rht-B1c (dwarfing) and was related to leaf water content and anatomy. Under drought, Rht-B1c line was characterized by less decreased CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
(65 reference statements)
1
18
1
Order By: Relevance
“…Other studies have reported proline accumulation in chickpea in response to drought and salinity, especially in tolerant genotypes [ 17 , 46 ]. The correlation between enhanced levels of photosynthetic enzymes [ 55 ] and proline content may have increased photosynthesis, biomass, and yield more in the T genotype than the S genotype under dehydration stress [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported proline accumulation in chickpea in response to drought and salinity, especially in tolerant genotypes [ 17 , 46 ]. The correlation between enhanced levels of photosynthetic enzymes [ 55 ] and proline content may have increased photosynthesis, biomass, and yield more in the T genotype than the S genotype under dehydration stress [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other traits, under well-watered experiments, dwarf and semi-dwarf plants with mutant alleles of Rht genes also show slower early growth of seedlings and young plants (Addisu et al, 2009), smaller epidermal cell size (Botwright, Rebetzke, Condon, & Richard, 2005), thicker leaves (Nenova et al, 2014), less chlorophyll and efficiency of photosynthesis (Jobson, Johnston, Oiestad, Martin, & Giroux, 2019), shorter spikes and anthers (Okada et al, 2019), and finally, reduced above-ground biomass, albeit with a higher HI than tall plants (Uppal & Gooding, 2013). Root weight was initially smaller in the earlier stages of growth in dwarf and semi-dwarf plants, with slower plant development (Bush & Evans, 1988), and higher differential abundance and association with rhizosphere bacterial communities was observed among the roots of tall plants compared to semi-dwarf wheats (Kavamura et al, 2020).…”
Section: Traits Affecting Growth Of Dwarf and Semi-dwarf Wheat Planmentioning
confidence: 99%
“…The Rht genes affect leaf size with a resultant decrease in leaf area of the whole plant (King, Gale, & Quarrie, ). In our earlier study on wheat Rht ‐near‐isogenic lines, we showed that compared to plants with the wild allele, the dwarf mutant Rht‐B1c plants had thicker leaves, less leaf area and higher density of stomata and trichome, and under induced drought stress exhibited greater tolerance evidenced by better preserved leaf water balance, more sustained membrane integrity, mobilized antioxidant defence and osmoregulation, and less affected photosynthetic activity (Kocheva et al., ; Nenova et al., ). Another semi‐dwarfing gene— Rht8, which is mostly distributed in warmer and drier environments (Chebotar, Korzun, & Sivolap, ; Ganeva, Korzun, Landjeva, Tsenov, & Atanasova, ) also leads to reduced cell elongation and reduced organs size, possibly, due to lower sensitivity to brassinosteroids (Gasperini et al., ).…”
Section: Introductionmentioning
confidence: 96%